Device for implantation of long-term transvenous cardiac pacemaker electrodes - Caves, P. K. (1970)
General anaesthesia is usually recommended for the most painful part of long-term transvenous pacemaker implantation, viz., the pulling subcutaneously of the end of the electrode from the neck incision to the site of pacemaker implantation. The ability to perform this step, and therefore the whole procedure, under local anaesthesia is an advantage. We describe a simple, inexpensive device which permits implantation of long-term transvenous cardiac pacemaker electrodes under local anaesthesia. Its use reduces operating time, pain and bleeding and avoids the dangers of general anaesthesia. The device and our implantation technique, as used in 58 patients, are described in detail. The device consists of a solid steel rod introducer and a slightly modified Mousseau Barbin tube (Porges 5870).